B1a and B2 cells are characterized by distinct CpG modification states at DNMT3A-maintained enhancers - Vinay S. Mahajan (Nature Portfolio, 2021)
B cell progenitors differentiate into multiple subsets with distinct functions. Here the authors analyze the epigenetic landscapes of sorted B cell subsets using multiple platforms and show that the epigenetic regulator, DNMT3A, is essential for modulating the activity of enhancers critical for B1 and B2 lineage-determining genes.